An In Vitro Pilot Study Investigating the Antineoplastic Effects of GP-2250 on Cutaneous Squamous Cell Carcinoma Cell Lines: Preliminary Results - Milan Barras; Lutz Schmitz; Chris Braumann; Waldemar Uhl; Marina Skrygan; Marie Buchholz; Thomas Meyer; Eggert Stockfleth; Thomas Müller; Jürgen C. Becker; Thilo Gambichler (MDPI AG, 2023)
Advanced cutaneous squamous cell carcinoma (cSCC) can be a life-threatening disease for which effective and safe treatment in advanced stages is very limited. GP-2250 has been recently proven to have-in vitro and in vivo-antineoplastic effects on cancer cells. This study aims to investigate the potential anti-neoplastic effects of GP-2250 on the cSCC cell lines SCC13 and A431 through dose finding assessments, MTT cytotoxicity assays, cell migration assays, BrdU proliferation assays and FCM analysis. Our preliminary results have shown for the first time evidence for anti-neoplastic effects of GP-2250 on cSCC cells, enhancing cytotoxicity, attenuating cancer cell proliferation, inducing apoptosis and reducing tumour cell migration. Further investigations evaluating the modes of action of GP-2250 on cSCC cell lines are warranted in order to justify the use in vivo studies.